Turkey - Joint Poverty Assessment Report : Volume 1. Main Report - World Bank (Washington, DC, 2012)
This report sets out a new poverty line methodology for Turkey, as the basic measure of poverty in the country. However, several poverty lines are calculated for the purpose of international comparability, and comparability to the Bank's poverty measures, using the 1987 and 1994 data. The basic data used in Volume One are from the official 2002 Household Budget Survey (HBS). The analysis refers generally to the new poverty line methodology that results in 27 percent poor. This line is called "complete" poverty line, and is referred to as "Total poverty" in statistical tables. An in-depth analysis of the 2002 Household Budget Survey (HBS) compared to that from 1994, shows that living standards in Turkey remained almost unchanged. Poverty based on the previous methodology declined gradually from 1987 to 2002, from 38.5 percent to 34.5 percent. Poverty based on the updated methodology declined from 28.3 percent to 27 percent from 1994 to 2002. On the other hand, marginal inequality increased. Extreme poverty, already low, further declined from 1994 to 2002. Food poverty declined from 2.9 to 1.4 percent, while $1 per person per day poverty, depending on purchasing power parity (PPP) used, was 2-3 percent, or even negligible (0.2 percent). The poverty-growth decomposition demonstrated that while economic growth was a main driving force in poverty reduction, much of the gains from growth were offset by inequality, which slightly worsened from 1994 to 2002. The timing of the two major surveys in Turkey - 1994 and 2002 - dictates the frame for the comparisons. Unfortunately, due to the macroeconomic instability, living standards between these two years have not improved. The conclusion that stems from this analysis is therefore that growth between 1994 and 2002 was not sufficiently strong to produce any sizable reduction in poverty, and the impact of the little growth there was, was dampened by an increase in inequality.